Exploring the Representational Competence of Eleventh-Grade Students on the Rates of Chemical Reactions - Phajan, Thetipat; Cojorn, Kanyarat; Ton Nu Nha Dien (Universitas Negeri Semarang, 2025)
Representational competence is a key component in learning chemistry, allowing students to interpret and apply multiple forms of representations to explain scientific phenomena. This competence supports deeper understanding, improved communication, and enhanced problem-solving. This study aimed to examine eleventh-grade students’ representational competence on the topic of chemical reaction rates. Data were collected using a short answer question with five scenarios, assessing five: 1) interpreting the meanings of chemical representations; 2) translating between different representations at the same level; 3) translating between different representations across levels; 4) using representations to generate explanations; and 5) connecting between representations and concepts. Descriptive statistics (mean, percentage, and standard deviation) were used for analysis. The results revealed an overall average score of 11.97 out of 30 (39.91%), indicating a moderate level of competence. While 78.95% of students performed at a moderate level and 21.05% at a low level, none reached a high level. Average scores by component showed moderate levels for interpreting representations (60.96%), generating explanations (51.75%), translating across levels (41.23%), and within levels (33.33%). The lowest performance was in connecting representations with concepts (12.28%), categorized as low. The findings suggest that students struggle particularly with integrating representations and concepts. Therefore, educators should design learning activities that explicitly connect multiple representations to conceptual understanding. This study provides insight into specific areas of difficulty and highlights the need for instructional strategies that target representational competence in abstract chemical topics, offering a practical contribution to chemistry education.